Innovation and Transformation of PT Telekomunikasi Indonesia: Colonial Legacy to Global Market - Rahmat, Rhin Khairina; Marghanita, Clara Lucia; Murti, Safira Nur Lathifah Eka (Prospect Publishing, 2024)
The telecommunications market in Indonesia is proliferating to become the backbone of the national economy. PT Telekomunikasi Indonesia, PT Telekomunikasi Indonesia, Tbk. Alternatively, (Telkom) has undergone a significant transformation from infrastructure management in the Dutch Colonial era to a leading digital service provider in Indonesia and even the global market. From a concessionary strategy of international expansion, as well as multinational collaborations, Telkom increases its competitiveness and supports Indonesia's digital economy. Telkom invests in global infrastructure, such as the Sea Cable Communication System (SKKL), and operates various international business schemes through its subsidiary, Telkom Indonesia International (Telin). This paper is analysed using the Network Approach concept to compare patterns of industrial cooperation between countries. The findings in this paper are that private involvement and the role of government are needed to overcome market failure in a country. Telkom's transformation includes changes in ownership and cooperation that enable adaptation to evolving market dynamics, strengthening its position as a leader in the regional and global telecommunications sector.